Transcriptome sequencing and network pharmacology-based approach to reveal the effect and mechanism of Ji Chuan Jian against Parkinson's disease - Yao Wu; Yu Bai; Yan Lu; Zhennian Zhang; Yang Zhao; Sirui Huang; Lili Tang; Yan Liang; Yue Hu; Chengcheng Xu (BMC, 2023)
Abstract Background Ji Chuan Jian (JCJ), a classic Traditional Chinese Medicine (TCM) formula, has been widely applied in treating Parkinson's disease (PD) in China, However, the interaction of bioactive compounds from JCJ with the targets involved in PD remains elusive. Methods Based on the transcriptome sequencing and network pharmacology approaches, the chemical compounds of JCJ and gene targets for treating PD were identified. Then, the Protein-protein interaction (PPI) and "Compound-Disease-Target" (C-D-T) network were constructed by using of Cytoscape. Gene Ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were applied to these target proteins. Finally, AutoDock Vina was used for applying molecular docking. Results In the present study, a total number of 2669 differentially expressed genes (DEGs) were identified between PD and healthy controls using whole transcriptome RNA sequencing. Then, 260 targets of 38 bioactive compounds in JCJ were identified. Of these targets, 47 were considered PD-related targets. Based on the PPI degree, the top 10 targets were identified. In C-D-T network analysis, the most important anti-PD bioactive compounds in JCJ were determined. Molecular docking revealed that potential PD-related targets, matrix metalloproteinases-9 (MMP9) were more stably bound with naringenin, quercetin, baicalein, kaempferol and wogonin. Conclusion Our study preliminarily investigated the bioactive compounds, key targets, and potential molecular mechanism of JCJ against PD. It also provided a promising approach for identifying the bioactive compounds in TCM as well as a scientific basis for further elucidating the mechanism of TCM formulae in treating diseases.